2022
DOI: 10.25048/tudod.1198697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of First Trimester Fasting Blood Glucose, HOMA-IR and HbA1c in Prediction of Gestational Diabetes Mellitus in Non-Obese Pregnant Women: A Retrospective Study

Abstract: Aim: Gestational Diabetes Mellitus (GDM) is the most common endocrine complication in pregnancy with fetomaternal comorbidities. It is aimed to evaluate fasting blood glucose (FBG), homeostasis model assessment of insulin resistance (HOMA-IR), and hemoglobin A1c (HbA1c) values in the first trimester in non-obese pregnant women for early detection of GDM. Material and Methods: Pregnant women with first-trimester FBG, HOMA-IR, HbA1c values, and second-trimester OGTT results were scanned from the hospital d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In other studies, the sensitivity of HOMA-IR for predicting GDM is much lower. In the study by Kirlangiç et al and our study, the sensitivity of HOMA-IR was found to be 63.6% and 61.1%, respectively (22).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In other studies, the sensitivity of HOMA-IR for predicting GDM is much lower. In the study by Kirlangiç et al and our study, the sensitivity of HOMA-IR was found to be 63.6% and 61.1%, respectively (22).…”
Section: Discussionsupporting
confidence: 49%
“…The predictive value of the HOMA-IR index in early pregnancy for predicting GDM development has been examined in several studies. In some of these studies, the HOMA-IR has been a strong predictor, while in other studies, its predictive value was moderate (19)(20)(21)(22). In the studies by Ozcimen et al and Alptekin et al, the sensitivity of HOMA-IR for GDM occurrence was reported as 100% and 90%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The results of this study also emphasize the importance of early diagnosis and good management of GDM, which could also reduce the risk of preterm birth. Additional use of some markers from the first trimester can also facilitate GDM diagnosis and could also reduce the risk of preterm birth and its related adverse outcomes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%